Эффективный метод анализа диагностических признаков по зашумленной электрокардиограмме - Файнзильберг, Л.С.; Матушевич, Н.А. (Управляющие системы и машины, 2016)
Предложен метод анализа основных электрокардиографических признаков ЭКГ на основе построения конструктивного алгоритма описания циклов сигнала совокупностью несимметричных гауссовых функций. Разработан конструктивный алгоритм решения задачи аналитическим методом, основанный на модификации критерия оптимальности метода наименьших квадратов и введения ограничения на интервал аппроксимации элементов сигнала. Представлены результаты численных экспериментов на модельных и реальных данных, подтвердившие эффективность предложенного алгоритма. Запропоновано метод аналізу основних електрокардіограмних ознак ЕКГ на основі побудови конструктивного алгоритму опису циклів сигналу сукупністю несиметричних гаусових функцій. Розроблено конструктивний алгоритм розв’язання задачі аналітичним методом, заснований на модифікації критерію оптимальності методу найменших квадратів і введення обмежень на інтервал апроксимації елементів сигналу. Представлено результати чисельних експериментів на модельних та реальних даних, котрі підтвердили ефективність запропонованого алгоритму. Introduction. Computer algorithms of ECG processing often lead to errors on the stage of measuring the diagnostic features focused on the informative fragments of ECG. Therefore, the actual task is a construction of the methods that enhance the reliability of the signs assessment of the real ECG that was distorted by the noise. The objective of the article is development of the ECG cycles approximation method by set of Gaussian functions, advancing on its basis a constructive algorithm ensuring an effective transition from the signal, observed on the conditions of the imposed external perturbations, to the diagnostic features system. Methods. The proposed method is based on model descriptions of ECG cycle as the sum of asymmetrical Gaussian functions. The determination of the optimal parameter values of the function based on the criteria of the Least Squares Method. The main electrocardiographic features are evaluated using the optimal parameters of the approximating function. Results: As the Gaussian function is nonlinear by parameters, for the practical realization the analytical method of evaluation optimal parameters, it is proposed to modify the optimality criterion moving from approximation of the actual data to their logarithms. For correct use of this approach, the original interval of approximation is narrowed to the desired value. The model experiments have shown that the modification criterion and introduction of the restrictions on interval of approximation allows an analytical solutions for estimating the parameters of the approximating functions from noisy data with the required accuracy. Even with a high noise level that in the experiments has reached 50% of the signal change range, mean square error of approximation was close to 1%. Conclusions: The proposed method provides the evaluation of the major electrocardiographic features of real signal with the necessary accuracy for their proper interpretation.